Supply Chain Impact on Consumer Confidence for Purchase Intentions Through Online - Bambang Nur Cahyaningrum; Akhirta Wulandari; Andiyas Miawan; Wisnu Untoro (International Journal of Supply Chain Management, 2020)
Abstract- Supply chain Management has played a significant role in corporate efficiency and has attracted the attention of numerous academicians over the last few years. This study aims to determine how the influence of supply chain, virtue, integrity, trust in intermediaries, trust in sellers, and customer loyalty, on purchase intentions through online. Data were obtained by distributing 168 questionnaires to students in the Soloraya region which included: Klaten Regency, Sukoharjo Regency, Wonogiri Regency, Sragen Regency, Boyolali Regency, and Solo Kota. The analytical tool used is SEM (Structural Equation Modeling). Based on the results of the analysis, it shows that the competency variable has no effect on trust in the intermediary. The variable of virtue and integrity, has a positive effect on trust in intermediaries. Variable trust in the intermediary has a positive effect on trust in the seller. The variable of trust in the intermediary and trust in the seller, has no effect, on purchase intention. The variable of trust in the intermediary, has a negative effect, on customer loyalty. Customer loyalty, has a positive effect on purchase intentions.